2023
DOI: 10.3390/healthcare11030446
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Technostress in the JD-R Model Perspective: A Systematic Literature Review

Abstract: This paper aims to describe the effects of Technostress on employees’ well-being and productivity. We adopted the Job Demands Resources Model as a theoretical framework to analyze the “Technostress” phenomenon in order to clarify whether and how technology can be considered a job demand, a job resource, or part of the effects of personal resources in the workplace. The sources search and selection process was conducted according to the PRISMA guidelines and regarded papers published from 2010 to 2022. Overall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…The JD-R model is a theoretical framework that explains how job demands and resources affect employee performance (Radic et al, 2020). According to the JD-R model, job demands refer to a job's physical, psychological, and social aspects that require sustained physical and mental effort and are associated with physiological and psychological costs (Pansini et al, 2023). On the other hand, job resources refer to those aspects of the job that are functional in achieving work goals and reducing job demands and are associated with motivation, engagement, and learning (Helal, 2022).…”
Section: Literature Review 1 Theoretical Backgroundmentioning
confidence: 99%
“…The JD-R model is a theoretical framework that explains how job demands and resources affect employee performance (Radic et al, 2020). According to the JD-R model, job demands refer to a job's physical, psychological, and social aspects that require sustained physical and mental effort and are associated with physiological and psychological costs (Pansini et al, 2023). On the other hand, job resources refer to those aspects of the job that are functional in achieving work goals and reducing job demands and are associated with motivation, engagement, and learning (Helal, 2022).…”
Section: Literature Review 1 Theoretical Backgroundmentioning
confidence: 99%
“…Their effects are also measured on employee activities such as the enrichment of knowledge at work, speed in managing les and shortening of processing times [7,8]. Other studies [9,10,11] have shown that the use of ICTs most often generates additional workload causing health problems for employees in organisations.…”
Section: Introductionmentioning
confidence: 99%
“…3,10,11 Others, look specifically at job demands changed by technology 4,12,13 and thus also consider different dimensions of the technostress model. The empirical findings are summarized in at least three recently published literature reviews, 4,10,11 which also reflect the hitherto largely unclear relationship between ICT use and burnout. 3,13,14 A meta-analysis by Baumeister et al 10 focuses on studies that examine the relationship between work-related ICT use and employee well-being, that is, burnout and engagement.…”
mentioning
confidence: 99%
“…Some studies consider the mere use of (new) technologies, especially information and communication technologies (ICT), as a stressor at work. 3,10,11 Others, look specifically at job demands changed by technology 4,12,13 and thus also consider different dimensions of the technostress model. The empirical findings are summarized in at least three recently published literature reviews, 4,10,11 which also reflect the hitherto largely unclear relationship between ICT use and burnout.…”
mentioning
confidence: 99%
See 1 more Smart Citation